Anti-psoriatic evaluation of aloe emodin-loaded topical hydrogel in an imiquimod-induced human plaque-type psoriasis in BALB/c mice - Ashish Pandey, Nimisha Srivastava, Ramesh Chandra Dubey, Suneela Dhaneshwar, Alok Kumar Shukla (Journal of Applied Pharmaceutical Science, 2024)
Aloe emodin, an anthraquinone derivative, mainly obtained from Aloe vera, possesses an extensive spectrum of pharmacological properties, including anti-proliferative, anticancer, wound healing, analgesic, anti-inflammatory, antibacterial, and antiviral properties. The objective of the present study was to prepare aloe emodin-loaded topical hydrogel formulations for managing plaque-type psoriasis. Different proportions of carbopol 940, chitosan, and hydroxyl propyl methyl cellulose K15M (HPMC K15M) were used as gelling agents. The prepared hydrogels were characterized for pH, viscosity, rheological behavior, spreadability, extrudability, swelling index, drug content, and accelerated stability. Based on physicochemical and in vitro permeation studies, PHGL1 containing aloe emodin (1%) and carbopol 940 (1%) was selected. The acute dermal toxicity study was also conducted as per the OECD guidelines 402. The mechanism of drug release followed Korsemeyer–Peppa’s model. The optimized batch showed a pH range from 6.867 ± 0.015 to 6.91 ± 0.254, drug content 94.6% ± 0.686% w/w of the active principle when studied in triplicate for drug content analysis, the measured viscosity of the formulation was 31402.33 ± 149.0783 mPaS exhibiting a shear thinning system along with thixotropic behavior at 25°C, and sustained drug release of 78% in 8 hours. An ex vivo permeation study demonstrated that 203.73 μg/ml/cm2 drug permeated through skin in 24 hours. Application of aloe emodin-loaded topical hydrogel to psoriatic skin resulted in a reduction of epidermal thickness, scaling, and ear thickness. The key inflammatory marker tissue necrosis factor (TNF-α) also showed a significant decrease. Compared with the marketed formulation, the test formulation showed no significant difference in the percentage reduction in ear thickness. No acute dermal toxicity was observed at the initial dose of 200 mg. The outcome suggests the promising potential of aloe emodin-loaded hydrogel in improving plaque-like psoriasis without dermal toxicity. Further studies are warranted to establish its efficacy in the management of psoriasis.
Keywords: Anthraquinone, Aloe vera, formulation, PASI score, carbopol 940, skin inflammation